Wacana Filosofis Pendidikan Islam Tentang Islam Kontemporer - Fauziah, Ardillah; Permatasari, Nabila Eka; Ramadhani, Dimas (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In response to the various changes and challenges faced by Muslims in the modern era, the discourse of contemporary Islamic educational philosophy emerged. This discussion is used to review the philosophical foundations of Islamic education and build a new direction that is relevant to the context of the times. The discussion on the philosophy of Islamic education in the modern era is still developing and has not reached an agreement. But this discourse has changed thinking about Islamic education significantly and paved the way for future Islamic educational reform.